Crop-animal systems in Asia: Importance of livestock and characterisation of agro-ecological zones - Devendra, C.; Thomas, D. (Elsevier, 2002)
Crop-animal systems, in which livestock play a multi-purpose role, are the backbone of Asian agriculture. In the future, increased productivity from livestock will be necessary in these systems to meet the increased demand for animal products, to alleviate poverty and to improve the livelihoods of resource-poor farmers. Agriculture in the region is characterised by diverse and complex production systems, which reflect the wide range of physical environments. In Southeast Asia, the main agro-ecological zones are characterised by humid/sub-humid climates, whilst those in South Asia are arid/semi-arid. Irrigated agriculture is well developed in high potential areas but, with the exception of Pakistan, the countries still depend heavily on rain-fed production systems. Most soils are of low fertility and some, such as the vertisols, present management problems. The natural vegetation consists of forests and native grasslands, with the latter more common in South Asia. Land degradation is a major concern and threatens the sustainability of the farming systems